PEMAHAMAN MASYARAKAT TENTANG GERHANA PERSPEKTIF ILMU FALAK - Burhanuddin, Andi Heny Wahyuni; Akmal, Andi Muhammad (HISABUNA: Jurnal Ilmu Falak, 2025)
The main problem of this research is how does the community understand the eclipse in Sumbang Village, Curio District, Enrekang Regency from a astronomical perspective? The main problem is then broken down into several sub-problems, namely: What is the reality of the community's understanding of eclipses in Sumbang Village, Curio District, Enrekang Regency. The type of research used is field research with the research approaches used are theological-normative (syar'i), juridical and sociological. The data sources for this research are traditional leaders, community leaders, religious leaders, Head of KUA and Village Imam. Furthermore, the data collection methods used were observation, interviews and documentation. Then, data processing and analysis techniques are carried out through three stages, namely: data reduction, data presentation and drawing conclusions. The results of this research show that there are people in Sumbang Village who do not know how the eclipse occurs, so their understanding still comes from the perspective of their ancestors. As the development of science changes people's opinions, for those who are educated, eclipses are considered a natural phenomenon that shows a sign of the power of Allah swt. From the astronomical perspective, an eclipse is considered a natural phenomenon destined by Allah swt. to show His majesty and greatness, which is not connected with certain myths or beliefs, as well as the time to carry out worship related to the eclipse as exemplified by the Prophet Muhammad. The implication of this research is that it is hoped that the public will be able to understand the eclipse well without associating this phenomenon with various beliefs or myths. And it is hoped that the attention of Falak experts will spread information and teaching about solar and lunar eclipses to the community in Sumbang Village widely.